Genetic analysis and heterotic grouping of quality protein maize (Zea mays L.) inbred lines and derived hybrids under conditions of low soil nitrogen and drought stress (2023)
Quality Protein Maize (QPM) varieties are rich in lysine and tryptophan, but suffer reduced grain yield (GY) in West and Central Africa (WCA) due to low soil nitrogen (low-N) and intermittent drought stress (DS). Development of stress-tolerant QPM hybrids will enhance sustainable maize production and improve nutritional health in WCA. Knowledge of combining ability, gene action and heterotic grouping of QPM inbred lines are crucial to successful breeding strategies for the development of superior hybrids with enhanced nutritional values. The objectives of this study were to: (i) determine the combining ability for GY and yield-related traits among 13 newly developed QPM inbred lines, and (ii) assign the QPM inbred lines to distinct heterotic groups based on general combining ability effects of multiple traits under low-N and DS conditions. Seventy-eight single cross hybrids were generated through half-diallel mating of 13 QPM inbred lines.